Fortalecimiento de la competencia léxica a partir de la expresión oral en inglés con estudiantes de grado décimo. (2021)
This final dissertation aims to provide a systematization of the experience of creation and adaptation process of the work "The Procession Goes Inside" second space "Passport to Heaven Century" by the author José Domingo Garzón, as a result of the academic spaces of Joint Assembly of Dance and Theater of the Bachelor in Artistic Education with Emphasis in Dance and Theater of the University Antonio Nariño, in which a reconstruction and reflection of the process is performed, highlighting the most important triggers that contributed to creation.